Water infiltration in methylammonium lead iodide perovskite: fast and inconspicuous - Müller, Christian; Glaser, Tobias; Plogmeyer, Marcel; Sendner, Michael; Kowalsky, Wolfgang; Pucci, Annemarie; Lovrinčić, Robert (Chemistry of materials, 2015)
While the susceptibility of CH3NH3PbI3 to water is well-documented, the influence of water on device performance is not well-understood. Herein, we use infrared spectroscopy to show that water infiltration into CH3NH3PbI3 occurs much faster and at a humidity much lower than previously thought. We propose a molecular model in which water molecules have a strong effect on the hydrogen bonding between the methylammonium cations and the Pb-I cage. Furthermore, the exposure of CH3NH3PbI3 to the ambient environment increases the photocurrent of films in lateral devices by more than 1 order of magnitude. The observed slow component in the photocurrent buildup indicates that the effect is associated with enhanced proton conduction when light is combined with water and oxygen exposure.